Exploring the psychosocial challenges faced by pregnant teenagers in Ditsobotla subdistrict - Peaceful N. Ntshayintshayi; Leepile A. Sehularo; Isaac O. Mokgaola; Nombulelo V. Sepeng (AOSIS, 2022)
Background: Pregnant teenagers usually experience psychosocial challenges such as a great amount of stress when they have to deal with an unwanted pregnancy, unpreparedness for parenthood and a lack of income as well as labour and birth complications. These are further complicated by the stigma from their families, friends and community. Unaddressed psychosocial challenges during teenage pregnancy can adversely affect the health outcomes of both mother and the child. Aim: This study explores and describes the psychosocial challenges faced by pregnant teenagers in the Ditsobotla subdistrict. Setting: The study was conducted in three health centres in the Ditsobotla subdistrict. Methods: A qualitative-exploratory-descriptive and contextual research design was used. Non-probability purposive and convenience sampling techniques were used to select the participants. Semistructured individual interviews through WhatsApp video calls were used to collect data, which were analysed using conventional content analysis. Results: Three themes emerged from the findings of the study, namely psychological challenges, social challenges and suggestions to address psychosocial challenges faced by pregnant teenagers. Conclusion: The findings established that pregnant teenagers in the Ditsobotla subdistrict are faced with psychosocial challenges which negatively impact their psychological health and social life. Suggestions made in this study have the potential to improve the psychosocial well-being of pregnant teenagers in the Ditsobotla subdistrict if implemented. Contributions: The findings of this study provide important information that may be used to improve the psychosocial well-being of pregnant teenagers in the Ditsobotla subdistrict.